INNER PRODUCT ON QUOTIENT SPACE OF TENSOR PRODUCT INDUCED BY STANDARD 2-INNER PRODUCT - YUDHI ANGGORO , ANTONIUS
This thesis discusses a construction of an inner product on a quotient of tensor prod- uct induced by standard generalized 2-inner product. It is done as a part of studying generalized 2-inner product by inner product on quotient of tensor product. Generally, a generalized 2-inner product only induce bilinear semi positive denite. It means that we need to construct a quotient of tensor product to get an inner product. Further, this thesis also discusses a generalization of relation between inner product, norm of vector, and angle between two vectors, in generalized 2-inner product context.